PENGARUH KEPADATAN KANDANG TERHADAP PERFORMA PRODUKSI AYAM PETELUR FASE AWAL GROWER - Dwi Erfif Gustira; Riyanti .; Tintin Kurtini (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The objective of this paper was to define the laying chicken production performance in the different stocking densities by evaluation of the feed intake, daily gain, feed convertion, uniformity and income over feed cost (IOFC).The completely randomised design was used in the research , A total 210 of 7 weeks old Isa Brown laying chicken were housed in the boxes in slatt rearing system at density of 6, 9, 12 and 15 birds/ m2 with 5 repition of each treatment. Result of trial indicate that stocking density had no significane effect on their feed intake, daily gain, feed convertion, uniformity and income over feed cost (IOFC). Consequently, the same production could be achieved by laying chicken with different stocking density (6,9 ,12 and 15 birds/m2 ) in the early grower phase.